Five Moment of Hand Hygiene Practices among Community Healthcare Workers in Primary Healthcare Facilities in Ebonyi North Senatorial District, Ebonyi State - Elom, Nwamaka Agbe; Alegu, Deborah Nnebuife; Okpata, Onyekachi Ogba; Ojide, Rita Ngozika; Matthias-Ede, Uzoamaka Mercy; Odo, Clementina, O. (International Journal of Human Kinetics, Health and Education, 2022)
This study investigated the demographic differences in the practices of five moments of hand hygiene among community healthcare workers in primary healthcare facilities in Ebonyi North senatorial district of Ebonyi State. The study used cross-sectional survey design and the entire population of 513 community healthcare workers in primary healthcare facilities in Ebonyi North senatorial district participated in the study. Structured questionnaire titled “Practices of Five Moments of Hand Hygiene Questionnaire” (r=0.89) was used for data collection. Mean, standard deviation and Analysis of Variance statistics were used to analyze the data. Results showed that both senior, junior community health extension worker and chief health officer in primary healthcare facilities in Ebonyi North had poor practice of five moments of hand hygiene. However, those with work experience 1-10years, 11-20years, and 21years and above had poor practice but 11-20years and 21years and above had good practice only on hand washing after touching a patient. Furthermore, there was no statistical significant difference in the practices of five moments of hand hygiene based on job status (P>0.05), but statistical significant difference was observed based on work experience (P<0.05). The study concluded that the community healthcare workers had poor practice of five moments of hand hygiene. Therefore, recommended among others that Ministry of Health in collaboration with Officers-In-Charge in primary healthcare facilities should organize educational programs to address the issue of poor hand hygiene especially to JCHEW and to those with 1-10years work experience.